Interactive numerals. Issue 4 (26th April 2017) - Thimbleby, Harold; Cairns, Paul
Abstract : Although Arabic numerals (like '2016' and '3.14') are ubiquitous, we show that in interactive computer applications they are often misleading and surprisingly unreliable. We introduceinteractive numerals as a new concept and show, like Roman numerals and Arabic numerals, interactive numerals introduce another way of using and thinking about numbers. Properly understanding interactive numerals is essential for all computer applications that involve numerical data entered by users, including finance, medicine, aviation and science.